Site Effects Mikrozonasi dan Regangan Geser Saat Gempa yang memicu Longsor Menggunakan Pengukuran HVSR di Kecamatan Ulu Mana Kabupaten Bengkulu Selatan Indonesia - Darmawan Ikhlas Fadli; Isfardian Agustin Awaliyah; Arif Ismul Hadi; M Farid; Arya J Akbar; Refrizon Refrizon (Jurnal Penelitian Pendidikan IPA, 2023)
The Ulu Manna area is classified as an area with high landslide potential because of its location and geological structure, which is hilly. The risk of landslides in the Ulu Manna area due to earthquakes in weak areas can be studied using ground shear strain (GSS). This study aimed to provide information on the potential of landslides in the Ulu Manna area, South Bengkulu Regency Indonesia. The data was collected using the Horizontal-to-Vertical Spectral Ratio (HVSR) method. The study area is 195.8 km2 and consists of 32 data collection points. The data processing was performed using WinMASW 5.2 HVSR and ArcGIS Desktop 10.8.2 software to obtain dominant frequency values, amplification values, subsurface soil vulnerability index values, maximum soil acceleration values, and soil shear strain values. The soil shear strain values obtained are on the order of 10-4 to 10-3, meaning that the dynamic characteristics of the soil in the study area are elastic-plastic. This plastic-elastic nature characterizes the area as an area with high landslide potential